Introduction: the AFL's Rule 35 - Gorman, Sean; Lusher, D.; Reeves, K. (Taylor & Francis, 2016)
This introductory paper lays the foundation for this important work. This is the first time that a multidisciplinary, systematic study has been conducted into the Australian Football League's (AFL) Rule 35 1. In 2013, due to the expanding nature of the initiative to encompass a range of themes and issues around vilification, the AFL updated the rule, known as Rule 30 since its inception, and in 1995, it became Rule 35. The difference between AFL ‘Rules’ and AFL ‘Laws’ is this: the rules relate more to the administration of the game, whereas the laws refer to the actual game itself (i.e. umpiring decisions). View all notes – the first code of conduct introduced by an elite sporting organization in the world to deal with racial, religious and sexual vilification. Social and sport history in Australia will be discussed to further contextualize the importance of the research.